2005
DOI: 10.1242/dev.01667
|View full text |Cite
|
Sign up to set email alerts
|

Shield formation at the onset of zebrafish gastrulation

Abstract: During vertebrate gastrulation, the three germ layers, ectoderm, mesoderm and endoderm are formed, and the resulting progenitor cells are brought into the positions from which they will later contribute more complex tissues and organs. A core element in this process is the internalization of mesodermal and endodermal progenitors at the onset of gastrulation. Although many of the molecules that induce mesendoderm have been identified, much less is known about the cellular mechanisms underlying mesendodermal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
201
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(222 citation statements)
references
References 42 publications
15
201
2
4
Order By: Relevance
“…As the fish swims, the current of the river carries it passively downstream, so its path is diagonally across and downstream in the river. A similar situation is documented in the zebrafish embryonic shield, where the ectoderm moves vegetalward while the adherent mesoderm travels animalward over it (Montero et al, 2005). If the fish can move between fast, deep and slow, shallow currents (the analog of mesoderm switching adhesion between the overlying ectoderm and the underlying YSL), then the fish's path is intermittently dependent on the ectoderm.…”
Section: Genetic Regulation Of the Early Convergence And Extension Momentioning
confidence: 67%
“…As the fish swims, the current of the river carries it passively downstream, so its path is diagonally across and downstream in the river. A similar situation is documented in the zebrafish embryonic shield, where the ectoderm moves vegetalward while the adherent mesoderm travels animalward over it (Montero et al, 2005). If the fish can move between fast, deep and slow, shallow currents (the analog of mesoderm switching adhesion between the overlying ectoderm and the underlying YSL), then the fish's path is intermittently dependent on the ectoderm.…”
Section: Genetic Regulation Of the Early Convergence And Extension Momentioning
confidence: 67%
“…Previous analyses have shown that E-cadherin is required for process formation, but its potential role on process orientation has not been analyzed (15). By using a morpholino directed against E-cadherin, we similarly found that morphant cells transplanted to a WT host form fewer cytoplasmic extensions (Fig.…”
mentioning
confidence: 61%
“…The prechordal plate has been described as a cohesive group, the cohesion of which is thought to be required for effective migration (15,16). However, most studies have focused on the anterior-most cells of the plate, and the architecture of the moving group has thus not been analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, gastrulation starts at around 50% epiboly, a point at which the blastoderm has spread and covered half of the large yolk cell, and with the internalization of hypoblast cells near the blastoderm margin at the dorsal side of the gastrula. These earliest internalizing cells form anterior axial mesendodermal (prechordal plate) tissue, expressing the homeobox gene goosecoid (gsc), while cells later internalizing at the dorsal blastoderm margin become chordamesoderm (notochord precursors), expressing the homeobox gene floating head (flh) (Dougan et al, 2003;Gritsman et al, 2000;Montero et al, 2005;Warga and Kimmel, 1990;Warga and Nusslein-Volhard, 1999). Progressive single cell ingression and convergence movements, causing cell compaction at the dorsal blastoderm margin, lead to the formation of the embryonic organizer (shield), the analog of the amphibian Spemann organizer (Dougan et al, 2003;Feldman et al, 1998;Gritsman et al, 2000;Montero et al, 2005;Schier and Talbot, 1998;Solnica-Krezel, 2006).…”
mentioning
confidence: 99%